Strengthening The Competitiveness of Indonesian Industry Human Resources Through IQF-Based Workplace Learning - Wardhana, Mada Aditia; Lestari, Endah; Nikmah, Musilatin (Universitas Pendidikan Nasional, 2024)
This study develops a Workplace Learning (WPL) model based on the Indonesian Qualification Framework (IQF) to enhance workforce competitiveness in Indonesia’s industrial sector. Addressing the existing competency gap between workforce skills and industry demands, this research integrates formal, informal, and experience-based learning approaches. Using grounded theory, data were collected from state-owned fertilizer companies, including annual reports and HR policy documents. The findings reveal that a combination of structured training, mentoring, on-the-job training, job rotation, and industry practice significantly boosts workforce competencies. Certification processes and managerial support, including career planning and competency-based recruitment, emerge as critical elements in aligning learning programs with industry needs. The developed model not only adheres to national standards but also aligns with global demands, fostering innovation, employee engagement, and long-term competitiveness. This study provides practical insights for industries and governments to design sustainable human resource development strategies. The proposed model highlights the importance of integrating WPL with national qualification frameworks, ensuring workforce adaptability and productivity in facing rapid technological advancements. Companies can leverage this model to build a more resilient and agile workforce, while policymakers may use it to bridge skill gaps and drive economic growth. By aligning education, training, and industry practices, the study contributes to improving labor mobility and promoting equitable workforce development, ultimately positioning Indonesia’s industrial sector competitively in the global market.